APPLICATION OF THE FUNGIC FORMULATION ARTHROBOTRIS OLIGOSPORA AGAINST THE NEMATODE DITYLENCHUS DESTRUCTOR - György SZABÓ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the year 2008 we started to use a microbiological product based on hyperparasite fungi, named Arthrobotris oligospora against nematodes, on several crops such as potatoes, carrots, parsley, knowing that this pests cause significant damages. We resorted to biological control, seeing as chemical control can be expensive. The purpose of the paper was the monitoring of and the decrease in the rate of the infestation caused by the nematode Ditylencus destructor from 43.2 % to 1.4%. Following application of the microbiological product in various quantities both in autumn and in spring, we reached an optimum dosage during the vegetative stage. The differentiated application of the microbiological product both in autumn, 1.5 kg and in spring, 1.5 kg led to the desired outcome. Based on the results obtained we concluded that in autumn, the product applied against nematodes has enough time to develop and infiltrate the soil to have the desired effect, i.e. capturing nematodes. This can actually be observed in the yield, when for a dose of 1.5 kg fungus / ha applied in the autumn, we obtain a healthy crop of 25.8 to/ha, and for 1.5 kg fungus /ha applied in the spring we obtain a healthy crop of 19.9 to/ ha. When using the fungus, the soil is not chemically loaded and it doesn’t present after-effects from other crops. The microbiological product based on A. oligospora has better results when the soil humidity reaches a saturation of 80%. On land with insufficient humidity, the results decline.